Oncogenic tuftelin 1 as a potential molecular-targeted for inhibiting hepatocellular carcinoma growth - Wu, Meng-Na (World J Gastroenterol, 2021)
BACKGROUND: Abnormal tuftelin 1 (TUFT1) has been reported in multiple cancers and exhibits oncogenic roles in tumor progression. However, limited data are available on the relationship between TUFT1 and hepatocellular carcinoma (HCC), and the exact biological mechanism of TUFT1 is still poorly understood in HCC. AIM: To investigate TUFT1 expression in HCC and how interfering TUFT1 transcription affects HCC growth. METHODS: TUFT1 in HCC and non-HCC tissues based on databases of the Cancer Genome Atlas and Oncomine were analyzed, and TUFT1 in human HCC tissues on microarray were detected by immunohistochemistry for clinicopathological features, overall survival, and disease-free survival. HCC cells were transfected with constructed vectors of TUFT1 that interfere or over-express TUFT1 for analyzing the biological behaviors of HCC cells. Proliferation, invasion, migration, and apoptosis of cells were detected by cell counting kit-8, scratch assay, transwell tests, and flow cytometry and confirmed by Western blotting, respectively. RESULTS: Abnormal TUFT1 levels in databases expressed in HCC at messenger RNA (mRNA) level and HCC tissues were mainly located in cytoplasm and membrane. The level of TUFT1 expression in the HCC group was significantly higher (χ(2 )= 18.563, P < 0.001) than that in the non-cancerous group, closely related to clinical staging, size, vascular invasion of tumor, hepatitis B e-antigen positive, and ascites (P < 0.01) of HCC patients, and negatively to HCC patients’ overall survival and disease-free survival (P < 0.001). After interfering with TUFT1 transcription at mRNA level in the MHCC-97H cells by the specific TUFT1-short hairpin RNA, cell proliferation, invasion, and metastasis were significantly inhibited with increasing apoptosis rate. In contrast, proliferation, invasion, and migration were significantly enhanced after over-expression of TUFT1 mRNA in Hep3B cells in vitro. CONCLUSION: Oncogenic TUFT1 was associated with the progression of HCC and could be a potential molecular-target for inhibiting HCC growth.